THE ROLE OF HUMAN CAPITAL IN THE INNOVATIVE DEVELOPMENT OF THE ECONOMY - Ataniyazov, Jasurbek; Alimardonov, Elshod (International Journal of Psychosocial Rehabilitation, 2020)
the article discusses the role of human capital in the innovative development of the economy, the priority directions of innovative development of the national economy, and offers recommendations for creating an effective innovation infrastructure to ensure the practical implementation of the results of scientific research in the field of the national and global economy